Integrated analysis of genome, metabolome, and transcriptome reveals a bHLH transcription factor potentially regulating the accumulation of flavonoids involved in carrot resistance to Alternaria leaf blight - Claude Emmanuel Koutouan; Marie Louisa Ramaroson; Angelina El Ghaziri; Laurent Ogé; Abdelhamid Kebieche; Raymonde Baltenweck; Patricia Claudel; Philippe Hugueney; Anita Suel; Sébastien Huet; Linda Voisine; Mathilde Briard; et al. (PLoS ONE, 2025)
Resistance of carrot to Alternaria leaf blight (ALB) caused by Alternaria dauci is a complex and quantitative trait. Numerous QTL for resistance (rQTLs) to ALB have been identified but the underlying mechanisms remain largely unknown. Some rQTLs have been recently proposed to be linked to the flavonoid content of carrot leaves. In this study, we performed a metabolic QTL analysis and shed light on the potential mechanisms underlying the most significant rQTL, located on carrot chromosome 6 and accounting for a large proportion of the resistance variation. The flavonoids apigenin 7- O -rutinoside, chrysoeriol 7- O -rutinoside and luteolin 7- O -rutinoside were identified as strongly correlated with resistance. The combination of genetic, metabolomic and transcriptomic approaches led to the identification of a gene encoding a bHLH162-like transcription factor, which may be responsible for the accumulation of these rutinosylated flavonoids. Transgenic expression of this bHLH transcription factor led to an over-accumulation of flavonoids in carrot calli, together with significant increase in the antifungal properties of the corresponding calli extracts. Altogether, the bHLH162-like transcription factor identified in this work is a strong candidate for explaining the flavonoid-based resistance to ALB in carrot.